Chemometrics Assisted LC-HRMS Non-Targeted Metabolomics for Discrimination of Beef, Chicken, and Wild Boar Meats - Windarsih, A.; Rohman, A.; Khasanah, Y.; Erwanto, Y.; Abu Bakar, N. K. (Tropical Animal Science Journal, 2024)
Meat authentication is very important to avoid adulteration, substitution, and mislabeling of meats and meat-based products to protect consumers by ensuring quality, safety, and halal status. This research aimed to employ metabolomics approach using liquid chromatography-high resolution mass spectrometry (LC-HRMS) to identify metabolites of beef (BM), chicken meat (CM), and wild boar meat (WBM) as well as to identify the discriminating metabolites of BM-WBM and CM-WBM. The chemometrics of principal component analysis (PCA) and partial least square-discriminant analysis (PLS-DA) were used to differentiate BM, CM, and WBM. The orthogonal projection to latent structures-discriminant analysis (OPLS-DA) was used to discriminate and identify discriminating metabolites of BM-WBM and CM-WBM through the variable importance for projections (VIP) value analysis (VIP>1.50, p<0.05). The heatmap plot showed the distribution of discriminating metabolites in BM, CM, and WBM samples. The results of this study suggested that untargeted LC-HRMS successfully identified metabolites in meats. In addition, chemometrics could be used to discriminate between BM, CM, and WBM clearly. In summary, the combination of LC-HRMS and chemometrics is promising for the authentication of meats to ensure the quality as well as halal status of meats.